Psikoedukasi Berbasis Self-Monitoring untuk Mengurangi Perilaku Phubbing pada Siswa/i SMA Ekayana Dharma Budhi Bhakti - Blessynki Barbara Tiara; Carissa Junietta Liman; Cindy Tan; Dominique Mysie Taroreh; Yohanes Budiarto (Pakis Journal Institute, 2026)
Phubbing behavior among adolescents has increased alongside growing smartphone use in daily life. Adolescents are particularly vulnerable to social interaction disruptions caused by this behavior, especially in school settings that demand active engagement and effective interpersonal communication. This study aimed to analyze the effectiveness of self-monitoring-based psychoeducation in reducing phubbing behavior among 10th-grade students at SMA Ekayana Dharma Budhi Bhakti. A quantitative pre-experimental design with a one-group pre-test post-test approach was applied to 25 students selected through purposive sampling. Data were collected using the Generic Scale of Phubbing (GSP) and Snyder's Self-Monitoring Scale, then analyzed using a Paired Sample T-Test in SPSS. Results indicated a significant improvement in students' self-monitoring ability (p = 0.030), with mean scores increasing from 27.88 to 30.20. Phubbing behavior decreased from 34.20 to 30.76, though not statistically significant (p = 0.053). Self-monitoring-based psychoeducation effectively enhances self-awareness and shows strong potential in reducing adolescent phubbing behavior.